International publishing in anaesthesia - how do different countries contribute? - Figueredo, E.; Sánchez Perales, G.; Muñoz Blanco, F. (Acta anaesthesiologica Scandinavica, 2003)
Background: The evaluation of the international distribution in biomedicine research is a subject that creates expectations. This study assesses the recent evolution of world‐wide distribution of research in the anaesthesiology field and discusses some of the possible factors which could give rise to changes in the interpretation of absolute results. Methods: A search on Medline was run to obtain the source country of the journal articles (with ) from 10 important anaesthesia journals in the 1997–2001 period. The data were analysed and standardized to journal impact factor values of each publication and population size. Annual evolution in the number of publications in the countries with the largest scientific production was analysed. Furthermore, the distribution of articles by country of origin was studied for each journal. Results: The 9724 publications came from 65 countries. In absolute numbers, the USA leads research in anaesthesiology (24.4%). The evaluation of the contribution of the more productive countries revealed a progressive increase in the German contribution (from 5.1% to 9.4%) and a decrease in the American contribution (from 28.6% to 21.8%) over the 5 years analysed. In relative terms, Finland, Sweden and Denmark were the most productive countries per million inhabitants (8.8, 7.2 and 6 publications/year, respectively). Conclusion: The geographic distribution of the publications on anaesthesiology must not only be analysed in absolute numbers, where the USA is the most productive. The North‐European countries show the largest production/number of inhabitants ratio; whereas the largest percentage increase during the period is found in Germany.